EFEKTIVITAS VARIASI UKURAN MEDIA ARANG AKTIF DAN ZEOLIT TERHADAP PENURUNAN KADAR BESI (Fe) PADA AIR SUMUR - Khulsum, Hanifah; Widiyanto, Agnes Fitria; Suratman, Suratman (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2018)
Background : Consumed water must be free from hazardous and toxic chemicals. The preliminary test showed that Fe of well water was 5.25 mg/l. Fe-contained well water must be processed zeolite and activated charcoal to decrease Fe in water. The purpose of this research was to find out the effectiveness of the size variation of zeolite and activated charcoal to decrease Fe of the well water in Desa Kebasen.. Method : The type of this research was quasi experiment, pretest posttest control group designwith a completely randomized design (CRD). Samples was 56 samples of well water contained Fe > 1 mg/l which chosen by random sampling method. The intervention in this research used 80, 100, and 120 mesh of zeolite and activated charcoal with 4 times repetitions for each treatment. The data analysis used normality test with Shapiro Wilk, Krusskal Wallis test, and Mann Whitney test Result : There was an average difference of Fe content before and after treatment used 80, 100, and 120 mesh of activated charcoal. There was an average difference of Fe content before and after treatment used 80, 100, and 120 mesh of zeolite. Conclusions : The 100 mesh zeolite was most effective at lowered Fe of well water in Desa Kebasen by 93.86%.